Strategi Pengembangan Agribisnis Melon (Cucumis Melo L.) Hidroponik di PT Indigen Karya Unggul, Kapanewon Kalasan, Kabupaten Sleman - Fahruddin, Ahnaf Rifqi; Sujono, Sujono; Prayoga, Adi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
One of the horticultural commodities in the Special Region of Yogyakarta with significant development potential is melon. The millennial generation is expected to replace the aging farmer population in Indonesia. This study focuses on company strategies to increase the interest of millennial farmers in entering the agricultural sector. The research was conducted at PT Indigen Karya Unggul, an agribusiness company established to attract millennials to agriculture. The millennial generation is considered essential for developing agribusiness enterprises, particularly at PT Indigen Karya Unggul.The research was carried out from December 2024 to February 2025 using a descriptive qualitative method. A literature review was conducted to formulate the strategies needed by the company as a means of agribusiness development. The findings are as follows: Based on the Cartesian diagram from the SWOT analysis, the intersection point lies at coordinates X,Y (-0.25; 0.345), placing it in quadrant III. This indicates that the strategy to be applied is the Weakness-Opportunities (W-O) strategy, also known as a conservative strategy, which represents a relatively favorable situation. The W-O strategy aims to minimize weaknesses by utilizing available opportunities